2560. Multispecies Outbreak of KPC-2 Producing Enterobacteriaceae in a Chilean Pediatric Hospital. (26th November 2018) - Rojas, Laura J; Marshall, Steven H; Rivas, Lina M; Spencer, Maria; Rutter, Joseph; Jacobs, Michael R; Perez, Federico; Coria, Paulina; Valdivieso, Francisca; Bralic, Rafael Araos; Munita, Jose M; Bonomo, Robert A
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) are a critical global health problem. We detected a surge of CRE cases in a pediatric hospital in Chile, a country with a low endemicity of KPC-producing organisms. Herein, we describe the molecular epidemiology of this outbreak. Methods: CRE isolates from clinical specimens and surveillance rectal swabs (obtained using chromID CARBA SMART agar, BioMerieux) of pediatric patients were collected from July 2015 to January 2017. Species identity was confirmed by MALDI-TOF. Carbapenemase genes ( bla KPC, bla NDM, bla VIM, bla IMP, and bla OXA-48-like ) were detected by multiplex PCR, followed by amplification and sequencing of the bla KPC allele. Conjugation experiments were conducted with representative species as donors and sodium azide-resistant E. coli J53 as recipient. PCR-based plasmid typing (PBRT Diatheva kit) was then performed on donors and recipients. For K. pneumoniae, genetic relatedness was investigated by PFGE, multilocus sequence typing and wzi typing. Results: Sixty-one CRE clinical and surveillance isolates were obtained from 49 patients aged 17 days to 16 years. bla KPC-2 was present in 57/62 isolates; no other carbapenemases were found. For 11 patients, multiple cultures were obtained; 4/11 had more than one KPC-harboring species. KPC-harboring isolates displayed ertapenem MICs ranging from 1 to >8 mg/L. Preliminary analyses suggest that bla KPC-2 is contained within a nonclassical Tn4401 structure (lacking the upstream promoter). Mating experiments indicate that bla KPC-2 is carried by a conjugative IncN backbone plasmid. Interestingly, K. pneumoniae isolates were nonclonal by PFGE and belonged to multiple STs unrelated to CG258 (ST34, ST36, among others) and different wzi types (37, 154, among others). Conclusion: We report a multispecies outbreak of KPC-2 producing CRE in children mainly driven by horizontal dissemination of a promiscuous IncN plasmid. The nonclonal, multispecies nature of this outbreak provides insights into the complex dynamics of KPC dissemination in countries like Chile, where the clonal spread of highly successful clones like CG258 is not the predominant dissemination vehicle, and instead HGT-related spread could be playing a more important role. Disclosures: All authors: No reported disclosures.